2013
DOI: 10.1016/j.elecom.2013.05.002
|View full text |Cite|
|
Sign up to set email alerts
|

Improving oxygen reduction reaction activity and durability of 1.5nm Pt by addition of ruthenium oxide nanosheets

Abstract: The durability of commercial carbon supported Pt nanoparticles with average particle size of 1.5 nm (20 mass% Pt/C) has been improved by the addition of ruthenium oxide nanosheets (RuO2ns) without sacrificing the initial activity towards oxygen reduction reaction.The initial oxygen reduction reaction activity of the composite catalyst was slightly higher than as-received Pt/C. The electrocatalytic activity after consecutive potential cycling tests of the composite catalyst was c.a. 1.3 times higher than non-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…We consider that the ORR activity shown by the reduced Pt nanoparticles on nanosheet contributes to the higher ORR activity retention rate in practical catalyst. As discussed in our previous papers, [10][11][12] RuO 2 nanosheet modified Pt/C electrocatalyst shows enhanced durability compared to non-modified Pt/C. Certainly, the degradation rate of carbon blacks used in practical catalysts and HOPG used in this model electrode study should be quite different due to the difference in degree of graphitization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider that the ORR activity shown by the reduced Pt nanoparticles on nanosheet contributes to the higher ORR activity retention rate in practical catalyst. As discussed in our previous papers, [10][11][12] RuO 2 nanosheet modified Pt/C electrocatalyst shows enhanced durability compared to non-modified Pt/C. Certainly, the degradation rate of carbon blacks used in practical catalysts and HOPG used in this model electrode study should be quite different due to the difference in degree of graphitization.…”
Section: Resultsmentioning
confidence: 99%
“…9 We have reported that the ORR activity and durability of commercial Pt/C are improved by the modification with RuO 2 nanosheets. [10][11][12] Because of the complex structure of the porous carbon support in commercial catalyst coupled with the ultimate thickness of the nanosheet of 1 nm, it was difficult to obtain conclusive evidence to explain the mechanism of the improvement on the catalyst durability. Therefore, studies of a simple model electrode system are desired to understand the enhanced durability of Pt/C electrocatalyst modified with RuO 2 nanosheets.…”
mentioning
confidence: 99%
“…We have recently shown that the durability of commercial Pt supported on carbon black can be enhanced with the addition of RuO 2 nanosheet. 17,18 Model electrode studies have elucidated that there is a strong electrostatic interaction between RuO 2 nanosheets and dissolved Pt ions derived electrochemically.19 This strong electrostatic interaction between ionic Pt species in solution and the nanosheets is considered to decrease the loss of dissolved Pt species into electrolyte due to migration.In this study, we present experimental evidence of a strong metalsupport interaction between RuO 2 nanosheet and metallic Pt, which may be another reason for the enhanced durability of RuO 2 nanosheet modified Pt/C. A model electrode system was employed to evaluate the difference in the adsorption strength of metallic Pt on RuO 2 nanosheet and carbon surfaces.…”
mentioning
confidence: 99%
“…We have recently shown that the durability of commercial Pt supported on carbon black can be enhanced with the addition of RuO 2 nanosheet. 17,18 Model electrode studies have elucidated that there is a strong electrostatic interaction between RuO 2 nanosheets and dissolved Pt ions derived electrochemically.…”
mentioning
confidence: 99%
See 1 more Smart Citation